Cybersecurity for executives : a practical guide - Touhill, Gregory J.; Touhill, C. J., 1938- (Hoboken, New Jersey : John Wiley & Sons, 2014)
This guide can be used by executives to make well-informed decisions on cybersecurity issues to better protect their business. It emphasizes, in a direct and uncomplicated way, how executives can identify, understand, assess, and mitigate risks associated with cybersecurity issues; covers what to do when you get hacked, including business continuity and disaster recovery planning, public relations, legal and regulatory issues, and notifications and disclosures; provides steps for integrating cybersecurity into strategy, policy and guidelines, change management and personnel management; identifies cybersecurity best practices that executives can and should use both in the office and at home to protect their vital information. --
6.3 WHAT IS IMPACTED BY CHANGE?6.4 CHANGE MANAGEMENT AND INTERNAL CONTROLS; 6.5 CHANGE MANAGEMENT AS A PROCESS; 6.5.1 The Touhill Change Management Process; 6.5.2 Following the Process; 6.5.3 Have a Plan B, Plan C, and maybe a Plan D; 6.6 BEST PRACTICES IN CHANGE MANAGEMENT; 6.7 SUMMARY; 7.0 PERSONNEL MANAGEMENT ; 7.1 FINDING THE RIGHT FIT; 7.2 CREATING THE TEAM; 7.2.1 Picking the Right Leaders; 7.2.2 Your Cybersecurity Leaders; 7.3 ESTABLISHING PERFORMANCE STANDARDS; 7.4 ORGANIZATIONAL CONSIDERATIONS; 7.5 TRAINING FOR SUCCESS; 7.5.1 Information Every Employee Ought to Know
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Computer networks -- Security measures; Computer networks -- Security measures; BUSINESS & ECONOMICS -- Industrial Management; BUSINESS & ECONOMICS -- Management; BUSINESS & ECONOMICS -- Management Science; BUSINESS & ECONOMICS -- Organizational Behavior; Computer networks -- Security measures; Computer networks / Security measures; Electronic books; Electronic books